Native mass spectrometry interrogation of complexes formed during targeted protein degradation - Ahmed, Ikhlas M. M.; Beveridge, Rebecca (Rapid communications in mass spectrometry, 2023)
Protein degraders are small molecules that promote cellular degradation of a target protein. Degraders simultaneously bind to their target and an E3 ligase, bringing them into close spatial proximity, but the formation of this ternary complex is difficult to measure with many biophysical techniques. Native mass spectrometry (nMS) is an effective label-free technique to identify the complexes formed by proteolysis-targeting chimeras (PROTACs). It can monitor the formation of ternary E3-PROTAC-target complexes and detect intermediate binary species. Experiments are described using a Synapt G2Si (Waters) equipped with a nano-electrospray ionisation source. The protocol describes nMS experiments for measuring the complexes formed by PROTAC molecules. It also describes how to investigate differences in the affinity of PROTAC complexes, whether a PROTAC shows specificity for a given target and whether a PROTAC shows cooperative behaviour. Here, we provide step-by-step instructions for the sample preparation of PROTAC complexes and their nMS interrogation to obtain optimal information on their binding modes.